Hak Kekayaan Intelektual Sebagai Jaminan Kredit: Analisis Sistem Hukum Pasca Berlakunya Peraturan Pemerintah Nomor 24 Tahun 2022 - Rifqi, Muhammad (Officium Notarium, 2025)
The Indonesian government has introduced the possibility of Intellectual Property Rights (IPR)-based financing through Government Regulation Number 24 of 2022 as part of its efforts to stimulate the growth of the creative economy. The regulation provides a legal framework for utilizing IPR as collateral in creative economy financing schemes through fiduciary security arrangements. Despite this regulatory advancement, its practical implementation remains constrained by various challenges. This study aims to analyze the legal and institutional obstacles that hinder the effective use of IPR as loan collateral within financial institutions. Employing a normative juridical approach and drawing upon Lawrence M. Friedman's legal system theory, which encompasses legal structure, legal substance, and legal culture, this research identifies three principal issues. First, from the perspective of legal structure, the absence of specialized IPR valuation institutions, secondary markets for collateral execution, and intermediary institutions limits the operational feasibility of IPR-based financing. Second, regarding legal substance, there is a regulatory inconsistency between Government Regulation Number 24 of 2022 and Bank Indonesia Regulation Number 14/15/PBI/2012, which does not explicitly recognize IPR as an acceptable form of collateral. Third, in terms of legal culture, limited public awareness of the economic value of IPR, coupled with the prudential principles adopted by financial institutions, generates reluctance to accept IPR as security for credit facilities. The findings indicate that without regulatory harmonization, the development of supporting infrastructure, and broader public awareness initiatives, the potential of IPR as a driver of creative economic growth will remain underutilized. Therefore, this study recommends the establishment of standardized IPR valuation guidelines, revisions to banking regulations, and the designation of selected financial institutions as pilot projects to accelerate the implementation of IPR-based financing schemes.